Continuous hydrogen regeneration through the oxygen vacancy control of metal oxides using microwave irradiation. Issue 66 (13th November 2018) - Seo, Keumyoung; Jeong, Sang-Mi; Lim, Taekyung; Ju, Sanghyun
Abstract : Continuous hydrogen generation could be performed using microwave irradiation with polyvinylpyrrolidone for low energy reduction. Abstract : The amount of hydrogen gas generated from metal oxide materials, based on a thermochemical water-splitting method, gradually reduces as the surface of the metal oxide oxidizes during the hydrogen generation process. To regenerate hydrogen, the oxygen reduction process of a metal oxide at high temperatures (1000–2500 °C) is generally required. In this study, to overcome the problem of an energy efficiency imbalance, in which the required energy of the oxygen reduction process for hydrogen regeneration is higher than the generated hydrogen energy, we investigated the possibility of the oxygen reduction of a metal oxide with a low energy using microwave irradiation. For this purpose, a macroporous nickel-oxide structure was used as a metal oxide catalyst to generate hydrogen gas, and the oxidized surface of the macroporous nickel-oxide structure could be reduced by microwave irradiation. Through this oxidation reduction process, ∼750 μmol g −1 of hydrogen gas could be continuously regenerated. In this way, it is expected that oxygen-enriched metal oxide materials can be efficiently reduced by microwave irradiation, with a low power consumption of <∼4% compared to conventional high-temperature heat treatment, and thus can be used for efficient hydrogen generation and regeneration processes in the future.